HIV screening among TB patients and co-trimoxazole preventive therapy for TB/HIV patients in Addis Ababa: facility based descriptive study. - Amenu Wesen Denegetu; Bethabile Lovely Dolamo (PLoS ONE)
Background Collaborative TB/HIV management is essential to ensure that HIV positive TB patients are identified and treated appropriately, and to prevent tuberculosis (TB) in HIV positive patients. The purpose of this study was to assess HIV case finding among TB patients and Co-trimoxazole Preventive Therapy (CPT) for HIV/TB patients in Addis Ababa. Methods A descriptive cross-sectional, facility-based survey was conducted between June and July 2011. Data was collected by interviewing 834 TB patients from ten health facilities in Addis Ababa. Both descriptive and inferential statistics were used to summarize and analyze findings. Results The proportion of TB patients who (self reported) were offered for HIV test, tested for HIV and tested HIV positive during their anti-TB treatment follow-up were; 87.4%, 69.4% and 20.2%; respectively. Eighty seven HIV positive patients were identified, who knew their status before diagnosed for the current TB disease, bringing the cumulative prevalence of HIV among TB patients to 24.5%. Hence, the proportion of TB patients who knew their HIV status becomes 79.9%. The study revealed that 43.6% of those newly identified HIV positives during anti-TB treatment follow-up were actually treated with CPT. However, the commutative proportion of HIV positive TB patients who were ever treated with CPT was 54.4%; both those treated before the current TB disease and during anti-TB treatment follow-up. Conclusions HIV case finding among TB patients and provision of CPT for TB/HIV co-infected patients needs boosting. Hence, routine offering of HIV test and provision of CPT for PLHIV should be strengthened in-line with the national guidelines.